Injury Patterns and Psychological Traits of Patients With Self-Inflicted Wounds Produced by Punching Glass - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Background: Self-inflicted injuries are among the preventable forms of hand injury. Psychologic factors underlying these injuries have not been studied sufficiently. This study aims to reveal the extent of injury and the morbidity as well as the psychologic factors in a population of patients who intentionally injured themselves by punching glass. Methods: Patients seen and treated for glass punching injuries during a 4.5-year period were reviewed. The demographic data included the extent of injury, postoperative hospitalization time, and full recovery time. Their psychologic traits were analyzed by two questionnaires (Symptom Distress Check List and State-Trait Anger Expression Inventory) and through a psychiatric interview. The results were compared with a sex- and age-matched control group with accidental hand injuries. Results: The study group consisted of 36 patients. Mean age was 24.7 years. Most were men (n = 28), not married (n = 28), and living with their families. Half of them were unemployed. Twelve had only skin lacerations. The remaining 24 patients had a total of 45 tendon, 15 nerve, and 9 artery injuries. On an average, 46 days were required for full recovery. A second attempt of self-infliction was not reported. Twenty-one patients underwent questionnaires and psychiatric interview. The study group felt significantly higher levels of psychologic distress and hostility (p = 0.018 and p = 0.002, respectively). They also had higher levels of anger in daily life (p = 0.002). Clinical psychiatric evaluation failed to reveal any significant psychiatric disorder. Conclusion: Self-inflicted hand injuries increase the workload of emergency services and clinics involved in the treatment. Prevention is very difficult, especially when alcohol is not an underlying cause. A typical patient has hostile and disobedient characteristics and who easily expresses his anger. Happily, having suffered enough during their treatment these patients do not attempt a second self-infliction.
Keywords: Punching glass; Alcohol; Hand injury; Anger; hostility; HAND INJURIES; CONSEQUENCES